Pola makan berhubungan dengan sindrom metabolik pada lanjut usia di Poliklinik Geriatri RSUP Sanglah Denpasar - IGA Sagung Kusuma Dewi; I Dewa Putu Pramantara; Retno Pangastuti (Jurnal Gizi Klinik Indonesia, 2010)
Background: Food intake is a factor determining health status and risk for degenerative diseases including metabolic syndrome. The fundamental function of someone’s nutritional status in the process of the emergence of generative disease and metabolic syndrome can be identified through the effect of food to the prevalence of obesity, hypertension, dyslipidemia or glucose tolerance disorder.Objective: To identify the association between eating pattern and the prevalence of metabolic syndrome among the elderly at Geriatric Polyclinic of Sanglah Hospital Denpasar.Method: The study was analytic observational with matched case control study design using ratio 1:1. There were 80 samples consisting of 40 as control group and 40 as cases matched by age and gender. Eating pattern was identified through food frequency questionnaire and calculated and compared to the need. Statistical analysis used chi square and risk factors were measured using odds ratio (OR). Multivariate analysis used double logistic regression to find out risk factors dominantly affected metabolic syndrome.Result: The result of bivariate statistical test showed significant difference in the prevalence of metabolic syndrome (p < 0.05) for energy intake (OR: 9.1; CI95%: 1.9-43.8), protein (OR: 3.8; CI95%: 1.5-9.7), fat (OR: 3.8; CI95%: 1.1-13.2), carbohydrate (OR:11.4; CI95%: 2.3-54.2). The result of multivariate analysis showed that the variables having dominant risk and significant difference in the prevalence of metabolic syndrome were carbohydrate consumption (OR: 8.1; CI95%: 1.29–50.89), fat consumption (OR: 4.9; CI95%: 1.17-20.61) and protein consumption (OR: 3.9; CI95%: 1.27-12.30).Conclusion: There was difference in eating pattern, i.e. high consumption of carbohydrate, fat and protein which became risk factor for the prevalence of metabolic syndrome among the elderly at Geriatric Polyclinic of Sanglah Hospital Denpasar.